PENGARUH KESADARAN WP, PENGETAHUAN PAJAK, SANGSI PAJAK DAN AKUNTABILITAS PELAYANAN PUBLIK PADA KEPATUHAN WP KENDARAAN BERMOTOR YANG ADA DI KOTA MALANG - Dedi Mizwar Umar; Dwiyani Sudaryanti; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
With the development of today's era it is one that makes people motivated to be able to meet all their needs. One of the most important needs at this time is a means of transportation. Transportation is very important in order to facilitate all the affairs of the community. Transportation equipment such as motorized vehicles is no longer a luxury item among the people, because we already know that many people in the middle and lower classes already have many motorized vehicles.The sampling technique was carried out using the purposive method with 120 respondents who were taxpayers in the city of Malang. Hypothesis testing was carried out using multiple linear regression analysis. The results of this study indicate that taxpayer awareness, tax knowledge, tax sanctions and accountability of public services have a positive effect on taxpayer compliance with motorized vehicles in the city of Malang.Keywords : Tax Awareness, Taxpayer Knowledge, Public Service Accountability, Tax Sanctions, Taxpayer Compliance